Preoperative evaluation of pulmonary hypertension in lung transplant candidates: echocardiography versus right heart catheterization. (14th October 2021) - Skalsky, K; Abu, T; Levi, A; Bental, T; Hirsh, R; Samara, A; Vaknin-Assa, H; Perl, L; Codner, P; Rosengarten, D; Kramer, M R; Kornowski, R; et al.
Abstract: Background: Right heart catheterization (RHC) and echocardiography are both routinely used for pulmonary hypertension (PH) assessment in LT candidates, although this is not mandatory according to guidelines. We aim to describe the correlation between the pulmonary artery systolic pressure (PASP) measured by echocardiography to that measured by RHC in this population. Methods: From a retrospective registry of 461 LT candidates, undergoing RHC between 2015–2019, 393 consecutive patients were assessed for the presence of pulmonary hypertension according to two methods – echocardiography and RHC. The primary outcome was the correlation between the estimated PASP measured by echocardiography to that measured by RHC. Secondary outcome was the accuracy of the echocardiographic assessment of PH. Results: Patients were predominantly males (63.6%) with a mean age of 61.46±8.33y. The two most common etiologies for lung failure were interstitial lung disease or pulmonary fibrosis (52.2%) and chronic obstructive pulmonary disease (30.5%). Estimated PASP as measured by echocardiography was available in 89.31% of the patients, with a mean value of 49.5±20.02 mmHg. Mean PASP measured by RHC was 42.47±17.96 mmHg. The correlation between the two measurements was moderate (Pearson's correlation: r=0.609, p<0.01). The accuracy of the echocardiographic estimation of PASP was poor with >10 mmHg differences between the two values in 79.9% of the patients. Conclusions: In the pre-surgical evaluation of LT candidates, echocardiographic estimation of PASP has moderate correlation with the PASP measured by RHC and relatively poor accuracy. FUNDunding Acknowledgement: Type of funding sources: None.